Public policy in Asia : implications for business and government - Asher, Mukul G.; Newman, David, 1956 October 25-; Snyder, Thomas P. (Quorum Books, 2002)
In this text, experts in Asian economics, public management, law and the sciences explore critical issues that will have a role in future policy debates. Topics include growth, income security and fiscal reform; governance and public management; and technological innovation and the environment.